1990
DOI: 10.2337/diab.39.6.728
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Cutaneous Insulin Allergy Resulting From High-Molecular-Weight Insulin Aggregates

Abstract: Cutaneous insulin allergy remains a clinical problem despite the use of highly purified human insulins. We used in vitro lymphocyte-transformation studies to examine the reactivity of various insulin formulations in diabetic patients with (n = 4) and without (n = 8) cutaneous allergies. Nonspecific response to concanavalin A demonstrated a greater than 40-fold response in both groups. Control patients did not respond to the addition of commercial insulin preparations (stimulation index [SI] less than 4), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 21 publications
0
30
0
2
Order By: Relevance
“…Since our patient had an atopic background, allergic reactions should be more common to occur. Associations of insulin allergy with other allergies have been formerly discussed [5]. At first, the patient received human recombinant insulin (HRI) for that allergy is encountered in less than 1% of patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…Since our patient had an atopic background, allergic reactions should be more common to occur. Associations of insulin allergy with other allergies have been formerly discussed [5]. At first, the patient received human recombinant insulin (HRI) for that allergy is encountered in less than 1% of patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, several case reports regarding development of local and generalized insulin allergy on insulin analogue treatment have been published [24,27,[35][36][37]. On the other hand, it has been shown that persistent cutaneous insulin allergy resulted from high-molecular-weight insulin aggregates [38]. Rapid-acting insulin analogues revealed with an immediate dissociation of hexamer structure to monomers, so that they might be less antigenic [38,39].…”
Section: The Use Of Insulin Analoguesmentioning
confidence: 97%
“…On the other hand, it has been shown that persistent cutaneous insulin allergy resulted from high-molecular-weight insulin aggregates [38]. Rapid-acting insulin analogues revealed with an immediate dissociation of hexamer structure to monomers, so that they might be less antigenic [38,39]. Successful treatment of local and systemic insulin allergy has been reported with switching of insulin treatment to a rapidacting insulin analogue, namely insulin lispro [40][41][42][43], aspart [44,45] or glulisine [46].…”
Section: The Use Of Insulin Analoguesmentioning
confidence: 97%
“…[40][41][42][43][44] Regular injections of insulin can also cause long-term effects, such as depositions of insulin amyloid, which have been observed in diabetic patients after repeated injections. [45][46][47] In our studies, we produced insulin amyloids in the absence of Zn 2+ ions and under low pH conditions where the protein exists in the destabilized monomeric state. Moreover, we conducted the studies in the low protein concentration regime, which disfavors hexamer formation, especially in the absence of Zn 2+ ions.…”
Section: Introductionmentioning
confidence: 99%